Prototipe Sistem Peringatan Dini Kualitas Minyak Rem Pada Angkutan Barang Berbasis Arduino Uno - Wijatolah, Jalu Lutfi; Mukhtar, Agus; Burhanuddin, Aan (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2025)
This research focuses on the development of an Arduino Uno-based early warning system to monitor brake fluid quality in freight vehicles. This system uses a TDS sensor to detect water content in brake fluid in real-time, displays the results on a 2004 IIC LCD screen, and provides visual and audio warnings if the brake fluid quality is below the safe threshold. This research employs the Research and Development method, utilizing a Planning, Production, and Evaluation model, and is validated by experts in the fields of information technology, electronics, and vehicle testing. System performance is evaluated through calibration against the Habotest Brake Fluid Liquid Tester and achieves 100% accuracy on various test samples. This prototype is proven to be easy to operate, provides accurate warnings, and has high feasibility for integration into existing vehicle fleets without requiring significant modifications. This innovation is expected to encourage a culture of preventive maintenance and improve public transportation safety.